Ardisia scalarinervis E.Walker, a New Record of Medicinal Plant Species for Vietnam - Thi Dieu Huong, Hoang; Thi Mai Huong, Pham; Viet Cuong, Dang; Van Hieu, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 4DO - 10.25073/2588-1132/vnumps.4752, 2025)
Abstract: Introduction: The genus Ardisia Sw. (ca. 730 species) primarily distributed in the tropical and subtropical regions of Asia. In Vietnam, about 100 species of Ardisia have been recorded. These plants have been used for a long time in traditional medicine to treat arthritis, liver, and stomach conditions, or as an herbal tea. Additionally, some Ardisia species have been reported to possess various biological effects, including antibacterial, antifungal, antioxidant, cytotoxic, and anti-inflammatory. Objective: This study aimed to identify the scientific names of medicinal plants in Muong Nhe district, Dien Bien province. Methods: Species identification was conducted based on morphological characteristics, using descriptions in the references, particularly those from type specimens. Results: Ardisia scalarinervis was recorded as a new species in the flora of Vietnam. A. scalarinervis E.Walker was characterized by stems densely reddish stramineous, long villous-tomentose, petiole 1-4 cm long, densely blackish or rusty tomentose or villous, glabrous adaxially, sparsely and minutely puberulent abaxially, inflorescences ca. 3 cm long, and pedicel ca. 1.5 cm long. A. scalarinervis was also used in folk medicine like the others in the genus Ardisia. Conclusion: Through a survey of medicinal plant resources in Muong Nhe district, Dien Bien province, this study has added a new medicinal plant to the Vietnamese flora. This group of plants holds significant medicinal value; however, it faces the threat of extinction due to overexploitation, the small number of individuals in the wild, and their narrow distribution area. Further research on breeding, cultivation, and conservation plans is essential for their protection in the future. Keywords: Ardisia scalarinervis , newly recorded species, Muong Nhe.